Gender‐specific differences in the development of sarcopenia in the rodent model of the ageing high‐fat rat. Issue 2 (30th April 2015) - Kob, Robert; Fellner, Claudia; Bertsch, Thomas; Wittmann, Astrid; Mishura, Daria; Sieber, Cornel C.; Fischer, Barbara E.; Stroszczynski, Christian; Bollheimer, Cornelius L.
Abstract: Background: Sarcopenia is linked to functional impairments, loss of independence, and mortality. In the past few years, obesity has been established as being a risk factor for a decline in muscle mass and function. There are several molecular pathological mechanisms, which have been under discussion that might explain this relationship. However, most studies were conducted using male animals and for a short period of time. Methods: In this study, the gender‐specific effect of long‐term, high‐fat content feeding in Sprague–Dawley rats was examined. Development of the quadriceps muscle of the animals was monitored in vivo using magnetic resonance. The results of these measurements and of the biochemical analysis of the aged muscle were compared. Results: Surprisingly, only male but not female rats showed a decline in muscle cross‐sectional area at 16 months of age as a result of a chronic oversupply of dietary fats. This loss of muscle mass could not be explained by either de‐regulation of the anabolic Akt pathway or by up‐regulation of the main ubiquitin ligases of muscle, MAFbx and MuRF‐1. However, fusion of satellite cells to myotubes was induced by the high‐fat diet in male rats, possibly as a result of an increased need for compensatory regeneration processes. Caspase‐3‐dependent apoptosis induction, irrespective of diet, seems to be the major determinant of muscle decline during ageing in male but not female rats. Conclusion: Taken together, activation of the apoptosis‐inducing Caspase‐3 seems to be the most important trigger for the age‐related muscle loss. Male rats were more prone to the decline of muscle during ageing than female animals, which was further enforced by a long‐term, high fat diet.